Safety, tolerability and pharmacokinetic properties of the novel triazene TriN 2755 in tumour bearing dogs – a phase I study†. (16th February 2015) - Athanasiadi, I.; Geigy, C.; Hilger, R. A.; Meier, V.; Rohrer Bley, C.
Abstract: TriN 2755 is an alkylating antineoplastic agent for intravenous (IV) use, carrying the triazene group as the cytotoxic principal. Using a standard 3 + 3 design, a phase I study was performed in tumour bearing dogs to determine the maximum tolerated dose (MTD), the dose limiting toxicity (DLT), and pharmacokinetic (PK) profile of TriN 2755. Thirty dogs were included in the study. TriN 2755 was administered over 20 min on two consecutive weeks per month for a total of three cycles. The starting dose was 25 mg kg −1 and the MTD was 74.6 mg kg −1 . Three dogs experienced DLT, which was characterized by gastrointestinal adverse events. The PKs of TriN 2755 and its main metabolites in plasma and sputum are described in a two‐compartment model. The response rate for 19 of 30 dogs was 47.3% (six partial remission, three stable disease) and the median progression‐free interval (PFI) for the responders was 47 days (range: 21–450 days).